Healthy, sustainable and plant-based eating: Perceived (mis)match and involvement-based consumer segments as targets for future policy. (May 2017) - Van Loo, Ellen J.; Hoefkens, Christine; Verbeke, Wim
Highlights: Perceptions of a healthy, a sustainable and a plant-based diet are strongly matched. Segments are identified based on involvement in healthy and sustainable eating. Involvement in sustainable eating implies involvement in healthy eating. The opposite does not consistently hold true. Abstract: Given the inseparable environmental and health impact of dietary habits, integrating health and sustainability goals has become a highly topical issue in policy development and communication to encourage consumers to adopt healthier and more sustainable diets. Increasing evidence indicates that it is possible to develop diets that are both environmentally sustainable and healthy, but their potential success largely depends on consumers' willingness and ability to change their behavior. This study investigates consumer perceptions of the match, or mismatch, between healthy and sustainable diets, and gives insight into consumers' motivation to eat healthily and sustainably, as measured by involvement. Data were collected in Spring 2014 through a cross-sectional quantitative online survey with samples representative for age, gender and region in four European Union (EU) countries (United Kingdom, Germany, Belgium, and the Netherlands) (n = 2783). The images of a healthy diet, a sustainable diet and a plant-based diet were found to be highly compatible based on a strongly observed match between European consumers' perceptions of these concepts. Half of the participants were highly involved in healthy eating and one third in both healthy and sustainable eating. Informational food policy actions targeting both healthy and sustainable food consumption behavior are recommended to address issues relevant to the target segments, taking into account their levels of involvement. Increasing consumers' motivation and involvement in health and sustainability emerges as a key trigger for increasing healthy and sustainable eating.